Cis‐trans proline isomers in the catalytic domain of calcineurin. (31st December 2018) - Teixeira, João M.C.; Guasch, Alicia; Biçer, Atilla; Aranguren‐Ibáñez, Álvaro; Chashmniam, Saeed; Paniagua, Juan Carlos; Pérez‐Riba, Mercè; Fita, Ignacio; Pons, Miquel
Abstract : Calcineurin is an essential calcium‐activated serine/threonine phosphatase. The six NMR‐observable methionine methyl groups in the catalytic domain of human calcineurin Aα (CNA) were assigned and used as reporters of the presence of potential cis‐trans isomers in solution. Proline 84 is found in the cis conformation in most calcineurin X‐ray structures, and proline 309, which is part of a highly conserved motif in phosphoprotein phosphatases, was modeled with a cis peptide bond in one of the two molecules present in the asymmetric unit of CNA. We mutated each of the two prolines to alanine to force the trans conformation. Solution NMR shows that the P84A CNA mutant exists in two forms, compatible with cis‐trans isomers, while the P309A mutant is predominantly in the trans conformation. Database: PDB depositions mentionedPDB 5C1V and2JOG . Abstract : 13 C‐enriched methyl groups of methionine residues in calcineurin can be selectively observed by NMR and are sensitive probes of their environment. The P84A calcineurin mutant, introduced to enforce a trans amide bond, shows a duplicated signal for methionine 191, compatible with the partial conservation of the natural cis conformation in the alanine mutant.